Rare Clinical Presentation of Acute Liver Injury and Symptomatic Seizure in Leptospirosis Infection: A Case Report - Marvell Aurelinus Artama; Carta Agrawanto Gunawan (The Indonesian Journal of Infectious Diseases, 2026)
Background: Leptospirosis is a zoonotic disease caused by bacteria from the genus Leptospira. It has a wide variety of clinical manifestations and could cause high morbidity if not diagnosed correctly. According to the Indonesian Health Profile Report in 2022, there were 1,419 cases of leptospirosis reported, with 139 deaths. Case Presentation: This study reports a case of leptospirosis in a 48-year-old male who presented with the main complaint of seizure. Prior medical history showed that he had a prolonged fever for more than 7 days. He worked as a farmer and lived in flood-prone areas. Physical examination showed icteric sclerae, tenderness in the upper right abdominal region, and pain in both calves. Laboratories showed acute liver injury, with highly elevated liver enzymes (ALT: 1408 U/dL, AST: 595 U/dL), without other severe manifestations, such as acute kidney injury or hemorrhage manifestations. The serology test showed a positive IgM antibody to Leptospira. The patient was treated with cefotaxime intravenously and other supportive therapies. After 10 days, the patient was discharged with improvement in clinical symptoms and laboratory parameters. Conclusion: Given its unusual presentations, diagnosing leptospirosis can be challenging, especially in tropical regions. This report aims to describe unusual findings in leptospirosis and to raise awareness of its possible etiology in a patient with acute liver injury, particularly in a high-risk individual in a tropical region.